2007
DOI: 10.4067/s0718-34292007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Produção De Mudas De Café ‘conilon’ Propagadas Vegetativamente Em Diferentes Níveis De Sombreamento

Abstract: RESUMOO café conilon (Coffea canephora) é uma cultura de grande importância na agricultura brasileira e ocupa posição de destaque entre os produtos de exportação. O cafeeiro pode ser conduzido em ambientes de baixa luminosidade, pois apresenta uma baixa irradiância de saturação. O trabalho teve como objetivo avaliar o crescimento de mudas de café conilon em diferentes níveis de sombreamento e a luz plena. O experimento foi realizado no CCA-UFES, Alegre/ES, no ano de 2005, num delineamento inteiramente casualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 7 publications
1
11
2
11
Order By: Relevance
“…BRAUN et al (2007), when evaluating "Conilon" coffee seedlings grown in different levels of shading, found the best results in the environment with 75% shading and in the present study for S1 the best results were found for the two screens with 50% shading, as verified by PAIVA et al (2003) in arabica coffee seedlings.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…BRAUN et al (2007), when evaluating "Conilon" coffee seedlings grown in different levels of shading, found the best results in the environment with 75% shading and in the present study for S1 the best results were found for the two screens with 50% shading, as verified by PAIVA et al (2003) in arabica coffee seedlings.…”
Section: Resultssupporting
confidence: 57%
“…In the seedling stage the plants require adequate agricultural substrates and protection against the climate, as well as appropriate management of irrigation, nutrition and pest control. Studies of substrates for the formation of coffee seedlings have been performed by ANDRADE NETO et al (1999), CUNHA et al (2002); FAVARIN et al (2008), MARANA et al (2008), , while studies with protected environments were conducted by CARELLI et al (1999), BRAUN et al (2007) and TATAGIBA et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pela hipótese levantada, a preocupação somente com Rd, visa a uniformizar a interceptação desta componente nas duas faces de exposição da linha de plantio, justamente por ser o cafeeiro uma cultura de ambiente sombreado, como citam BRAUN et al (2007) e TATAGIBA et al (2010, pois, no campo, não sendo possível cultivar em ambiente totalmente sombreado, ao menos que haja uniformidade da Rd incidente sobre a cultura.…”
Section: Desenvolvimento Do Modelounclassified
“…A radiação solar interceptada por uma cultura é uma importante variável meteorológica que determina sua transpiração e fotossíntese, necessitando ser avaliada e mais bem estudada (ANGELOCCI et al, 2008). De acordo com as citações de BRAUN et al (2007) e TATAGIBA et al (2010, sabe-se que o cafeeiro é uma planta C3, ou seja, é uma planta de ambiente sombreado, que possui adaptações fisiológicas e morfológicas para esse tipo de ambiente. PEZZOPANE et al, (2005) e PEZZOPANE et al (2007 realizaram um estudo efetuando medições da radiação solar e do saldo de radiação em cafeeiros cultivados a pleno sol e consorciados com bananeira e observaram atenuação média dos valores de radiação solar no sistema consorciado da ordem de 21%, com variação mensal de 16% a 27%.…”
Section: Introductionunclassified
“…To BRAUN et al (2007) the adaptation of plants to the environment of light depends of the adjustment of its photosynthetic apparatus, experiencing an adaptation of the same, which can be observed through its global growth.…”
Section: Introductionmentioning
confidence: 99%